Effect of Music with Brainwave Synchronizer on the Performance of Collegiate Throwing Athletes - Francis Mae L. Rebadomia; Jeremiah Seag Miguel G. Amparo; Jessa P. Reyes; Alvin George C. Cobar; Rhene A. Camarador (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2019)
Brainwave entrainment has been a method used as a therapy to reduce anxiety and heighten concentration, facilitating brain to enter a specific state. In sports, brainwave alignment is facilitated as athletes utilized music in their pre-competition routines. The aim of this study is to know if wave-synchronized music influence power performance of collegiate athletes by gathering six (N=6) college throwers, 3 males and 3 females in a quasi-experimental research. Participants ranged from shotput, discus and javelin events. With reversal method, throwing performance data were collected for 11 days, with treatment days using both high (T1, T2, T4) and low (T3) frequency waves after every 2 untreated observations. Results show that synchronizing alpha waves (12 Hz) to music listened by athletes during warm-up leads to significant increase in throwing distances of participants compared to the untreated trial performance. On the other hand, synchronizing theta waves (0.5-3 Hz) to music produced lower throwing distances significantly when compared to day-before and day-after observations. Throwing performance for the untreated observations also showed an increasing trend before the theta wave treatment day. However, no long-term effect of alpha waves was directly seen after the intervention as perceived in latter untreated observations. Further studies are needed to compare music with and without wave synchronizers or to compare the utilization of preferred music versus unfavored music during warm-up.